2010
DOI: 10.1016/j.ejvs.2010.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Results after Transfemoral Venous Thrombectomy for Iliofemoral Deep Venous Thrombosis

Abstract: It is safe and effective to treat extensive iliofemoral DVT using transfemoral venous thrombectomy and this prevents the development of severe PTS in the long term. The procedure is only feasible in a subset of patients with DVT, depending on the extent and the age of the thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 14 publications
(14 reference statements)
0
16
0
2
Order By: Relevance
“…Only Plate et al reported 10 year results prospectively and a patency rate of 83% after surgical thrombectomy [12]. These data have been confirmed by others and by our previously published results [1,13,16]. For example, Hölper et al reported primary and secondary patency rates after a mean follow-up of 64 month of 74% and 84% respectively [1] and Wagenhäuser et al described primary patency rates of 89% after a mean follow-up of 63 month [13].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Only Plate et al reported 10 year results prospectively and a patency rate of 83% after surgical thrombectomy [12]. These data have been confirmed by others and by our previously published results [1,13,16]. For example, Hölper et al reported primary and secondary patency rates after a mean follow-up of 64 month of 74% and 84% respectively [1] and Wagenhäuser et al described primary patency rates of 89% after a mean follow-up of 63 month [13].…”
Section: Discussionmentioning
confidence: 54%
“…Thus, a subgroup analysis of this study shows a benefit in the reduction of severe PTS for the use of pharmacomechanical catheter-directed thrombolysis, limited to patients with an iliofemoral DVT [11]. However, there have been demonstrated good results for surgical thrombectomy of iliofemoral DVT in terms of prevention of PTS as well [1,8,[12][13][14][15][16][17]. Even though duplex ultrasound mapping is the gold standard in the diagnosis of venous diseases including PTS [18], other noninvasive diagnostic methods e.g.…”
Section: Introductionmentioning
confidence: 97%
“…According to this case report, surgical glue removal was not successful due to the hard consistency of the glue and the associated risk of potential intraoperative complications such as vessel perforation, vessel rupture or pulmonary embolism [12]. Lindow et al [14] reported that the main determining factor in thrombectomy for iliofemoral thrombosis is the age of the thrombosis, since successful surgical removal of a thrombus is only possible up to a maximum thrombus age of ten days. Cyanoacrylate is a strong and fast-acting adhesive, thus even early surgical thrombectomy might not have been successful.…”
Section: Dear Editorsmentioning
confidence: 99%
“…It is worthwhile to mention that the thrombectomy procedure was without any ballooning or stenting but with a flow stimulating a-v fistula created in the groin (31). A German center with great experience has published important results with surgical thrombectomy in 83 patients with iliofemoral DVT in 2010 (32). In the last patients of the series, the procedure was added with distally infused rtPA via a foot vein.…”
Section: Surgical Thrombectomymentioning
confidence: 99%